Decreased Expression of Arginine-Phenylalanine-Amide-Related Peptide-3 Gene in Dorsomedial Hypothalamic Nucleus of Constant Light Exposure Model of Polycystic Ovarian Syndrome - Shaaban, Zahra (Int J Fertil Steril, 2018)
BACKGROUND: An abnormality in pulse amplitude and frequency of gonadotropin releasing hormone (GnRH) secretion is the most characteristics of polycystic ovarian syndrome (PCOS). On the other hand, arginine-phenylalanine-amide (RFamide)-related peptide-3 (RFRP3) inhibits the secretion of GnRH in mammalian hypothalamus. The current study performed in order to investigate the expression of RFRP3 mRNA in the dorsomedial hypothalamic nucleus (DMH) after the induction of PCOS in a rat model of constant light exposure, and the possible role of parity on occurrence of PCOS. MATERIALS AND METHODS: In the experimental study, female nulliparous (n=12) and primiparous (n=12) rats were randomly subdivided into control and PCOS subgroups (n=6). PCOS were induced by 90 days exposure to constant light. After 90 days, blood, brain, and ovaries were sampled. Serum levels of follicle stimulating hormone (FSH), luteinizing hormone (LH), and testosterone were evaluated. In addition, six adult female ovariectomized rats as a control of real-time polymerase chain reaction (PCR) tests were prepared and in the DMH of all rats, the relative mRNA expression of RFRP3 was assessed. RESULTS: Histological evaluation of ovaries represented the polycystic features. In addition, serum concentrations of testosterone in the PCOS subgroups were more than the controls (P<0.05). Furthermore, the relative expression of RFRP3 mRNA in PCOS subgroups was lower than the controls (P<0.05). CONCLUSION: Constant light model of the PCOS-induced rats decreased the gene expression of RFRP3 in the DMH that suggests the decrease of RFRP3 may reduce its inhibitory effect on GnRH during the PCOS pathogenesis. This effect was stronger in the nulliparous rats than the primiparous.